It takes two to tango the effects of television commercials that feature local celebrity love teams on the consumer behavior of Filipino teenagers. - Ventura, Camille Abigael M. 1988-
"This study aimed to understand how Filipino teenagers as media and product consumers are affected by television commercials that feature local celebrity love teams. The study also determined the teenagers' responses towards such type of commercials. Moreover, the study identified the teenagers' personal references, internal influences, external influences, information evaluation, purchase decision, and post-consumption evaluation. Furthermore, the study examined the advertising plan behind these television commercials. The Black Box Model of Consumer Behavior and the Consumer Decision Making Model were integrate to explain the phenomenon. The search conducted a survey among 200 selected high school students in Metro Manila. For an in-depth discussion, focus interviews were facilitated among eight rendomly selected survey respondents. To provide expert information, the study conducted focus interviews with two advertising representatives from the Accounts and Creative Department. The study found out that Filipino teenagers purchase, consume, and patronize products endorsed in television commercials that featured local celebrity love teams, but they do not buy these on a regular basis. The respondents prefer commercials that feature local celebrity love teams. Moreover, the respondents consider the love team endorsers as a huge factor in their purchase. Thus, this type of commercials has greatly influenced the consumer behavior of Filipino teenagers."